Program Peningkatan Kemampuan Bahasa Inggris Dengan Pendekatan Active And Fun Learning Bagi Siswa Sekolah Dasar - Tri Ananda, Herwin; Al Baqi, Safiruddin (Literasi Jurnal Pengabdian Masyarakat dan Inovasi, 2021)
English is a foreign language that is learned at all levels of education. Fun learning methods can make students active in learning and communicating in English. The aim of this program is to improve English skills for elementary students with an active and fun learning approach. This program used experimental method with one group pretest-posttest design, where all 13 students in fifth grade of SD N 1 Grogol are assigned to the experimental class. The implementation of this program consists of three stages, namely pretest, teaching and learning activities (treatment), and posttest. The mean score as the results of the pretest was 52.31 and the posttest was 83.46. The paired sample t-test showed a significance value of 0.000 (p < 0.05). These results indicate that there is an effect of using an active and fun learning approach in improving the English skills of fifth grade students at SD N 1 Grogol